2022
DOI: 10.1038/s41467-022-32450-6
|View full text |Cite
|
Sign up to set email alerts
|

High activity and selectivity of single palladium atom for oxygen hydrogenation to H2O2

Abstract: Nanosized palladium (Pd)-based catalysts are widely used in the direct hydrogen peroxide (H2O2) synthesis from H2 and O2, while its selectivity and yield remain inferior because of the O-O bond cleavage from both the reactant O2 and the produced H2O2, which is assumed to have originated from various O2 adsorption configurations on the Pd nanoparticles. Herein, single Pd atom catalyst with high activity and selectivity is reported. Density functional theory calculations certify that the O-O bond breaking is sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…Specifically, bimetallic PtPd and Au catalysts have received significant attention for the oxidation of sugars. Some of these systems could also benefit from the conversion of oxygen and hydrogen to hydrogen peroxide, which could be produced immediately upstream by using Au or PGM catalysts instead of using the anthraquinone process. , This approach could create a distributed source of hydrogen peroxide, which would save on the hazardous transport of high concentration hydrogen peroxide from centralized facilities. The availability of green oxygen and renewable electricity can also spur the production of on-demand ozone as another inexpensive oxidant with potential uses in the facile activation of C–H and C–C bonds to produce chemical precursors from emerging feedstocks. , …”
Section: Viable Catalytic Metals For Emerging Feedstocksmentioning
confidence: 99%
“…Specifically, bimetallic PtPd and Au catalysts have received significant attention for the oxidation of sugars. Some of these systems could also benefit from the conversion of oxygen and hydrogen to hydrogen peroxide, which could be produced immediately upstream by using Au or PGM catalysts instead of using the anthraquinone process. , This approach could create a distributed source of hydrogen peroxide, which would save on the hazardous transport of high concentration hydrogen peroxide from centralized facilities. The availability of green oxygen and renewable electricity can also spur the production of on-demand ozone as another inexpensive oxidant with potential uses in the facile activation of C–H and C–C bonds to produce chemical precursors from emerging feedstocks. , …”
Section: Viable Catalytic Metals For Emerging Feedstocksmentioning
confidence: 99%
“…108,109 These unique properties endow single-atom catalysts with dramatically enhanced catalytic performance 110,111 and an altered reaction pathway. 112,113 For example, Zhao et al 114 reported a single-atom Pt supported on MgO nanosheets (Pt SA/MgO) for toluene oxidation and investigated the activation process of O 2 . High-angle annular dark field-scanning transmission electron microscopy (HAADF-STEM) of Pt SA/MgO showed the presence of single-atom Pt, which was further confirmed by X-ray adsorption near edge structure (XANES) spectra of Pt L 3 -edge and Wavelet transformextended X-ray absorption fine structure (WT-EXAFS).…”
Section: Catalysis Science and Technologymentioning
confidence: 99%
“…7 Previous research indicates that palladium (Pd) is the most active catalyst for direct H 2 O 2 synthesis from H 2 and O 2 . 8,9 However, Pd nanoparticles (NPs) usually have a tendency to agglomerate during catalytic reactions, which results in a decrease in catalytic activity. 10 To solve the problem, Pd NPs usually are stabilized onto various porous supports.…”
Section: Introductionmentioning
confidence: 99%